Alterations of Vaginal Microbiota in Women With Infertility and Chlamydia trachomatis Infection - Chen, Hongliang; Wang, Li; Zhao, Lanhua; Luo, Lipei; Min, Shuling; Wen, Yating; Lei, Wenbo; Shu, Mingyi; Li, Zhongyu (Frontiers in Cellular and Infection Microbiology, 2021)
Chlamydia trachomatis (C. trachomatis) is the most common etiological agent of bacterial sexually transmitted infections (STIs) worldwide and causes serious health sequelae such as cervicitis, pelvic inflammatory disease, and even infertility if ascending from the lower to the upper female genital tract. Previous studies have revealed the pivotal role of vaginal microbiota in susceptibility to STIs. However, alterations in the vaginal microbiota in women who are infertile and infected with C. trachomatis remain unknown. This study used metagenomic analysis of sequenced 16S rRNA gene amplicons to examine the vaginal microbial profiles of women with tubal infertility who were C. trachomatis-negative and those who were C. trachomatis-positive pre- and post-antibiotic treatment. Women who were C. trachomatis-negative and deemed healthy were recruited as references of eubiosis and dysbiosis. Women with tubal infertility and C. trachomatis infection presented a unique Lactobacillus iners-dominated vaginal microbiota rather than one dominated by Lactobacillus crispatus and displayed a decrease in Lactobacillus, Bifidobacterium, Enterobacter, Atopobium, and Streptococcus, accompanied by decreased levels of cytokines such as interferon (IFN)-γ and interleukin (IL)-10. This altered vaginal microbiota could be restored with varying degrees after standard treatment for C. trachomatis. This shift could be a predictive vaginal microbiota signature for C. trachomatis infection among females with tubal infertility, while no significant differences in phylum, class, and operational taxonomic unit (OTU) levels were observed between women with tubal infertility who were C. trachomatis-negative and healthy controls. This is the first study to provide data on the association of vaginal microbiota with C. trachomatis infection among women with tubal infertility and highlights unprecedented potential opportunities to predict C. trachomatis infection.